A new genome allowing the identification of genes associated with natural variation in aluminium tolerance in Urochloa grasses - CGIAR Research Program on Livestock (2020)
Limited regulation of malate transporters suggests that exudation of organic acids and other external tolerance mechanisms, common in other grasses, might not be relevant in Brachiaria, and the contrasting regulation of RNA translation and response signalling indicates that response timing is critical in high Al3+-tolerant species. Proof of concept published.